Factors Contributing To University Students’ Integrity - Fazilah, Idris; Wardah, Mustafa Din; Mohammad Rezal, Hamzah; Jamiah, Manap; Rajan, Munusamy; Anita, Abdul Rani; Nur Aini Aiman, Zulkifli Airwan (Human Resource Management Academic Research Society (HRMARS), 2022)
Integrity is an essential value that university students should possess to ensure the advancement of organisations, the country and also the welfare of the community. However, the increase in cases of disciplinary misconduct among university students shows that their integrity is compromised and deteriorating. In addition, the views of a handful of students that accepting bribes is not an offense and expressed their willingness to accept bribes, revealed low level understanding on the concept of integrity. The aim of this study is to identify factors that contribute to instilling integrity in university students to develop a corruption-free generation. This study was conducted qualitatively using semi-structured interview to obtain more information and data. A total of 5 integrity specialists from Universiti Kebangsaan Malaysia (UKM), Universiti Malaysia Pahang (UMP) dan Universiti Malaysia Perlis (UniMAP) and 21 students were chosen as informants in this study. All the data and information were analyzed using Atlas.ti software. The study identified 3 main factors, namely religious internalization, the environment and self-identity. Hence, these elements should be included in student development programs, to prevent them from involving in activities that are dishonest and without integrity.